Osteopontin is an important mediator of alcoholic liver disease via hepatic stellate cell activation - Seth, Devanshi (Baishideng Publishing Group Inc, 2014)
AIM: To investigate over-expression of Osteopontin (OPN) pathway expression and mechanisms of action in human alcoholic liver disease (ALD), in vivo and in vitro acute alcohol models. METHODS: OPN pathway was evaluated in livers from patients with progressive stages of human ALD and serum from drinkers with and without liver cirrhosis. In vitro stellate LX2 cells exposed to acute alcohol and in vivo in acute alcoholic steatosis mouse models were also investigated for OPN pathway expression and function. WT and OPN(-/-) mice were administered an acute dose of alcohol and extent of liver injury was examined by histopathology and liver biochemistry after 16-24 h. The causative role of OPN was studied in OPN knockout animals and in vitro in stellate LX2 cells, utilizing siRNA, aptamer and neutralizing antibodies to block OPN and OPN pathway. OPN pathway expression and downstream functional consequences were measured for signaling by Western blotting, plasmin activation by spectrophotometric assays and cell migration by confocal imaging and quantitation. RESULTS: OPN expression positively correlated with disease severity in patients with progressive stages of ALD. In vivo, associated with alcoholic steatosis, a single dose of acute alcohol significantly increased hepatic OPN mRNA and protein, and a cleaved OPN form in a dose dependent manner. OPN mRNA and secreted OPN also increased in parallel with activation of LX2 stellate cells within 4 h of a single dose of alcohol. Expression of OPN receptors, αvβ3-integrin and CD44, increased in human ALD, and in vivo and in vitro with alcohol administration. This was accompanied by downstream phosphorylation of Akt and Erk, increased mRNA expression of several fibrogenesis, fibrinolysis and extracellular matrix pathway genes, plasmin activation and hepatic stellate cell (HSC) migration. Inhibition of OPN and OPN-receptor mediated signaling partially inhibited alcohol-induced HSC activation, plasmin activity and cell migration. CONCLUSION: OPN is a key mediator of the alcohol-induced effects on hepatic stellate cell functions and liver fibrogenesis.